2016
DOI: 10.1177/0886260515587664
|View full text |Cite
|
Sign up to set email alerts
|

Parental Support Buffering the Effect of Violence on Adolescents’ Depression

Abstract: In Mexico violence across the country has increased in recent years and has become a social problem of great importance. The continuous exposure to all types of interpersonal violence leads adolescents to cope with experiences and challenges of great risk of development deviations. Trying to find a more comprehensive understanding of violence outcomes on Mexican adolescents and its moderators, the present quantitative, non-experimental, cross-sectional correlation study was performed. Parental support ( vs. ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…One of the interesting findings was that males considered their parent to be more caring and warm than did females. This finding is consistent with those reported by Quiroga et al (2017), in that, males viewed their parents as being more supportive than females. However, for males, parental care did not predict their committing simple assault or aggravated assault, although perceived parental care was associated with less social aggression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One of the interesting findings was that males considered their parent to be more caring and warm than did females. This finding is consistent with those reported by Quiroga et al (2017), in that, males viewed their parents as being more supportive than females. However, for males, parental care did not predict their committing simple assault or aggravated assault, although perceived parental care was associated with less social aggression.…”
Section: Discussionsupporting
confidence: 92%
“…However, although these warm and low-control parenting methods may work in suburban and rural areas, “good” parenting strategies in urban centers that are low in social order and high in crime tend to be higher in control and lower in warmth to ensure the physical safety of these youth (Furstenberg, Cook, Eccles, & Elder, 2000). In a recent study, Quiroga, López-Rodriguez, and Willis (2017) reported that parental support appeared to moderate depression for girls who were exposed to violence, but had no effect for boys.…”
Section: Parental Bonding and Adolescent Depressionmentioning
confidence: 98%
“…Family support was found to moderate post-ECV internalized problems among girls and externalized problems among boys (Bacchini, Miranda, & Affuso, 2011). Furthermore, findings have shown that although family support moderates the association between ECV and depression among boys as well as among girls, the moderation effect is stronger among girls than among boys, especially following high levels of ECV (Quiroga, López-Rodríguez, & Willis, 2017). A longitudinal study conducted among a representative sample of children and adolescents in the United States showed that a positive relationship with the mother can moderate antisocial behavior after experiencing peer violence among girls, but not among boys (Yang & McLoyd, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This study highlights the importance of family and community intervention to promote mental health among the increasing population of multicultural adolescents. Parental support may protect adolescents from developing depressive symptoms after exposure to violence (Quiroga et al, 2017). Additionally, the provision of multiple channels of communication with family members or friends to discuss personal issues can be effective in helping adolescents overcome depressive symptoms (Lim et al, 2016).…”
Section: Community Supportmentioning
confidence: 99%
“…Even when research participants were not multicultural adolescents, previous research on the correlations and profiles of depressive symptoms among adolescents has focused on the following three categories (Lim et al, 2016; Osok et al, 2018): (1) demographic characteristics, including gender, economic status, academic status, and weight category (Chung & Joung, 2012; Lim et al, 2016); (2) psychological factors, including body image satisfaction and self-esteem (Chung & Joung, 2012; Lim et al, 2016; Senin-Calderón et al, 2017); and (3) social factors including family support, friendships and peer group support, and community support (Lim et al, 2016; Quiroga et al, 2017). Some research included multicultural adolescents (Bahk et al, 2017; G.…”
mentioning
confidence: 99%